2005
DOI: 10.1113/jphysiol.2005.087874
|View full text |Cite
|
Sign up to set email alerts
|

Activation of transient receptor potential vanilloid 1 (TRPV1) by resiniferatoxin

Abstract: Transient receptor potential vanilloid 1 (TRPV1) is a Ca2+ permeable non-selective cation channel activated by physical and chemical stimuli. Resiniferatoxin (RTX), an ultrapotent agonist of TRPV1, is under investigation for treatment of urinary bladder hyper-reflexia and chronic pain conditions. Here, we have determined the characteristics of RTX-induced responses in cells expressing native and cloned rat TRPV1. Whole-cell currents increase with repeated application of submaximal concentrations of RTX until a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 68 publications
7
100
0
2
Order By: Relevance
“…Even in a depolarized state, the mouse arterial mesenteric bed responded to PNS via a TTX-or capsaicin-sensitive reduction of perfusion pressure. Interestingly, capsaicin activates the transient receptor potential vanilloid 1 (TRPV1) as recently reviewed by Begg et al (2005) whereas Raisinghani et al (2005) have suggested that binding of capsaicin to its receptors can occur in a voltage-dependent fashion in patch-clamped-single-cell experiments. Our results on NANC-induced reduction in perfusion pressure in a complex vascular circuit under depolarized conditions can therefore be explained by the voltage-dependent increases in TRPV1 activation as previously put forward by Raisinghani et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Even in a depolarized state, the mouse arterial mesenteric bed responded to PNS via a TTX-or capsaicin-sensitive reduction of perfusion pressure. Interestingly, capsaicin activates the transient receptor potential vanilloid 1 (TRPV1) as recently reviewed by Begg et al (2005) whereas Raisinghani et al (2005) have suggested that binding of capsaicin to its receptors can occur in a voltage-dependent fashion in patch-clamped-single-cell experiments. Our results on NANC-induced reduction in perfusion pressure in a complex vascular circuit under depolarized conditions can therefore be explained by the voltage-dependent increases in TRPV1 activation as previously put forward by Raisinghani et al (2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that the anti-cancer effects of capsaicin are not to activate TRPV1 (Raisinghani et al, 2005), but to inhibit plasma membrane NADH oxidase (Morre et al, 1995). Moreover, alternative anti-cancer mechanisms of capsaicin have been associated with the production of reactive oxygen species (Qiao et al, 2005) and the reduction of TNF-α .…”
Section: Discussionmentioning
confidence: 99%
“…Resiniferatoxin (RTX) is an ultrapotent TRPV1 agonist, which activates TRPV1 in an irreversible manner. As a result, TRPV1 nerve terminals are ablated by persistent increase in Ca 2+ influx [5,[23][24][25]. Therefore, it would be useful to use RTX to target TRPV1 to *Address correspondence to these authors at the Department of Clinical Medicine, Michigan State University, Lansing, MI 48824, USA; Tel: 217-545-2179; Fax: 217-545-0145; E-mails: lpremkumar@siumed.edu and sqyu@msu.edu treat conditions such as peripherally mediated inflammatory pain including shingles, urinary bladder hyperreflexia, deiabetic peripheral neuropathy, arthritis etc.…”
Section: Transient Receptor Potential Vanilloid 1 (Trpv1) Is a Camentioning
confidence: 99%